(untitled) (International Conference on Economics, Business, and Management Research (ICEBMR), 2024)
Environmental, Social, and Governance (ESG) issues have evolved recently, although there has been little research on bibliometrics. The purpose of this study is to analyze and map the performance of ESG in the context of a sustainable blue economy through bibliometric analysis. We used the Scopus database for this research. Several bibliometric methodologies, including research trends, productive contributors, collaboration networks, and research focus areas, are integrated with topics to create an overview. The findings reveal that the literature on ESG in sustainable blue economy has grown significantly over the past few decades. The contributions of researchers worldwide represent interests that cross geographical boundaries and provide an overview of the global challenges. Mapping ESG performance in the sustainable blue economy using network visualization reveals three clusters of current hot issues. The red clusters are primarily concerned with blue economy conservation. The green cluster focuses on a company’s ESG performance, whereas the blue cluster relies on the environmental impact of its activity. These results provide a deeper understanding of research trends and gaps, as well as ESG performance development strategies for achieving a sustainable blue economy.